THE INVESTMENTS IN THE PURCHASE OF AGRICULTURAL LAND FOR THE PURPOSE OF REDUCING RURAL POVERTY - Todorović, Saša; Ivanović, Sanjin; Marković, Todor (Economics of Agriculture, 2011)
Family farms in the Republic of Serbia are characterized by unfavorable possession structure. A previous research has shown that the increase of land would contribute not only to better utilization of available labor force of family farm members, but it would also have many other favorable effects on business operations of the family farms, as well as on the whole rural economy. The lack of capital for investments in land purchase proves to be the greatest obstacle to the improvement of possession structure. Bearing this in mind, the research in this paper aims at determining the economic effectiveness of investments in the purchase of agricultural land. The results of the research show that the investment in land purchase in case of dominant fnancing with the borrowed capital and at high prices of land, are economically justifed only over a very long time period.